Review on Techniques Available for Segmentation and Labeling of Fractured Bones from CT Images - Nayan Chheda; Prekshaa Thakkar; Abhiraaj Jadhav (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The paper examines various approaches and techniques used for segmenting fractured bones from CT images, and evaluates the advantages and limitations of each method. It also delves into the labeling process of fractured bones and emphasizes the importance of expert involvement in accurately labeling the segments. Additionally, the paper highlights the challenges and potential outcomes of segmenting and labeling fractured bones in CT images. Overall, this review provides valuable insights into the state-of-the-art techniques for segmenting and labeling fractured bones from CT images, as well as the potential for future research in this area.